(untitled) (Vietnam Journal of Community Medicine, 2024)
Plectranthus amboinicus (Lour.) Spreng. is a perennial herb belonging to the Lamiaceae family. It was found naturally in tropical regions and widely cultivated in Vietnam for its leaves, which have a pleasant lemon-like fragrance and a flavor that was aromatic at first and later intense and cool. The plant was used as a spice and in traditional medicine to treat colds, asthma, constipation, headaches, coughs, fevers, insect bites, and skin diseases. A review of research both domestically and internationally indicates that essential oil is the main component of the plant, with a concentration ranging from 0.1% to 0.75%. The essential oil contains various compounds that depend on geographical characteristics such as soil type, climate, and humidity. Numerous studies have demonstrated biological activities such as effects on respiratory diseases, antibacterial and antifungal properties, antioxidant effects, larvicidal activity, and anti-cancer potential. This review article aims to provide information on the chemical composition and biological activities of P. amboinicus essential oil, focusing on recent studies. It also seeks to outline avenues for further research into the medicinal potential of this plant, particularly regarding its essential oil components.